A Food Chain with Lethal Prey (Global Journal of Science Frontier Research, 2019)
We form a model of a food chain in the chemist at where the prey species can defend itself against the predator by producing a toxin lethal to the predator. Numerically, we illustrate that if the toxin production by the prey is constant, toxin levels will not vary considerably. On the other hand, if the prey is able to adjust its toxin production based on the density of the predator, toxin levels can vary considerably and periodically. In the context of the biological example we reference, the results indicate that toxic algae blooms might be a regular and periodic occurrence in nature.
Keywords: chemostat; growth; predator; prey; toxin; toxic algae bloom